Integrating transport into 'joined-up' policy appraisal - Jones, P; Lucas, K (Elsevier, 2000)
In 1998 the UK Government published the first Transport White Paper for over 20 years, A New Deal for Transport; Better for Everyone. The document emphasised the need for joined-up policy thinking and for co-ordinated action across different areas of government, a theme that has been taken up in many subsequent policy documents issued by central government. The paper explores the extent to which ‘joined-up thinking’ is evident in practice, both in the ways in which transport measures are appraised (e.g. do they fully take into account non-transport impacts?), and in appraisals in other policy areas with significant transport impacts. It does so by examining appraisal frameworks in different sectors, and identifies a number of current weaknesses. It then builds on these examples to propose ways in which an integrated policy appraisal framework could be developed. This would aim to identify not only the comparative cost-effectiveness of different transport measures in fulfilling policy objectives, but also the relative contribution that different areas of government could make—including transport—to the delivery of over-arching policy objectives, such as sustainable development, social exclusion and regeneration.